2018
DOI: 10.2147/cmar.s156071
|View full text |Cite
|
Sign up to set email alerts
|

Combination of CRP and NLR: a better predictor of postoperative survival in patients with gastric cancer

Abstract: ObjectivesC-reactive protein (CRP) and neutrophil to lymphocyte ratio (NLR) were independent predictive factors for gastric cancer (GC). Our study was designed to prove the prognostic value of the combination of CRP and NLR (COC-NLR) in GC patients.Materials and methodsA total of 1,058 GC patients who underwent D2 resection from Sun Yat-Sen University Cancer Center between 2003 and 2013 were included. They were divided into three groups (low: NLR ≤2.5, CRP ≤6.1; medium: NLR >2.5, CRP ≤4.5; high: NLR >2.5, CRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 33 publications
0
43
1
3
Order By: Relevance
“…Similar to elevated platelet count, high PLR has been found to be associated with worse survival in a variety of solid (hepatocellular, ovarian, cervix, colorectal, bile duct, breast, lung, renal cell, gastric, prostate, and oesophageal) tumours [30][31][32][33][34][35][36][37][38][39][40]. Moreover, several studies confirmed the relationship between elevated NLR and a worse prognosis in patients with malignant oesophageal [41], colorectal [42,43], pancreas [44,45], prostate [46,47], hepatic [48,49], bile duct [50], breast [51], gastric [52,53], cutaneous melanocytic [54], thyroid medullary [55], and lung [56] tumours. It is important to note, however, that NLR may be elevated also in many benign disorders [57,58].…”
Section: Discussionmentioning
confidence: 88%
“…Similar to elevated platelet count, high PLR has been found to be associated with worse survival in a variety of solid (hepatocellular, ovarian, cervix, colorectal, bile duct, breast, lung, renal cell, gastric, prostate, and oesophageal) tumours [30][31][32][33][34][35][36][37][38][39][40]. Moreover, several studies confirmed the relationship between elevated NLR and a worse prognosis in patients with malignant oesophageal [41], colorectal [42,43], pancreas [44,45], prostate [46,47], hepatic [48,49], bile duct [50], breast [51], gastric [52,53], cutaneous melanocytic [54], thyroid medullary [55], and lung [56] tumours. It is important to note, however, that NLR may be elevated also in many benign disorders [57,58].…”
Section: Discussionmentioning
confidence: 88%
“…Systemic inflammation could be monitored by using peripheral hematologic markers, such as neutrophils, leukocytes and platelets. Based on the relationship between inflammation and cancer, in recent years, inflammatory marker-based scores, such as NLR and PLR have been reported to be associated with the prognosis of patients with various cancers, including lung cancer [8], breast cancer [10,23], gastric cancer [11,24] and colorectal cancer [25]. However, NLR and PLR only include two types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, these genomic technologies are expensive at present and more genomic information needs to be integrated due to the biological complexity of NSCLC [7]. Recently, systemic inflammatory response indicators, such as peripheral neutrophils, lymphocytes and platelets, play important roles in the progression and prognosis of various cancers, including lung cancer [8,9], breast cancer [10] and gastric cancer [11]. Moreover, these peripheral markers can be detected with an easy, convenient method, and its application in prognosis prediction deserves attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peviouse research have shown that Neutrophil to Lymphocyte ratio (NLR) being used as a biomarker for the prognosis of RCC [8] [9] . NLR was an indicator of general immune response to various stress, it has been proved to be a prognosis related marker in various malignancies, including RCC [10][11] [12] . Earlier meta-analysis on NLR in patients with metastasis renal cancer described that elevated baseline NLR remained an independent predictor of OS and PFS [13] .…”
Section: Introductionmentioning
confidence: 99%